COMPORTAMENTO DE AMAMENTAÇÃO DE BEZERROS NELORE E CRUZADOS - SANTOS, Camylla Silveira; CASTRO, Micheline Feitosa; QUEIROZ, Maria Carla Elias; ALMEIDA, Gabrielly Benevides; SILVA, Milena Vitória; OLIVEIRA, Dalton Mendes (ANAIS DO ENIC, 2024)
-